The Essential of Sustainable Building Construction Practices - Chandrasekaran Balaji Venkateswaran (Journal of Sustainable Construction Materials and Technologies, 2019)
The sustainable building practices are essential techniques considered in construction of buildings in order that the resources of the earth are not depleted and the resources are carried forward to the future generations. This paper discusses the essentials of sustainable building construction practices in India. The techniques through which the sustainability could be achieved i.e., alternate building technologies available for adoption, building materials suitable to achieve sustainability and renewable energy sources etc., are discussed.